(untitled) (London Journal of Engineering Research, 2023)
:In this study, in order to confirm the potential of coffee waste as a recyclable resource material, the caffeine content of coffee waste and the effective active ingredients of coffee waste extract were confirmed using an ultrasonic extraction method. In order to conduct a preliminary experiment to determine whether extraction of coffee waste affects caffeine reduction, ultrasonic extraction was performed after immersion at room temperature for 48 hours at ethanol content of 0%, 30%, 50%, 70%, and 100%. The coffee waste recovered after extraction were analyzed for active ingredients using GC-MS. Except for the coffee waste after extraction with 100% ethanol, almost no components other than caffeine were detected in the coffee waste recovered after extraction by ethanol content. As a result of quantitative analysis of caffeine in coffee grounds using LC-MS, a caffeine reduction rate of 72.1% was confirmed in the coffee grounds recovered after ultrasonic extraction with 70% ethanol.